Administrative Strategy For A Graduate School Of Administration - Gordon, Paul (Academy of Management Journal, 1967)
Graduate education alone, for administration in business, government, universities, or hospitals, increasingly fails to cover the needs of our kind of society and the requirement for improved discipline in the field. Many endeavors other than business as we know it in the United States have gotten to be big business the world around. Possibly even more true beyond our own borders, there are implications as well for people concerned with international, development, comparative, and general systems work.